2014
DOI: 10.7453/gahmj.2013.064
|View full text |Cite
|
Sign up to set email alerts
|

Serial Case Reporting Yoga for Idiopathic and Degenerative Scoliosis

Abstract: Background:Non-surgical techniques for treating scoliosis frequently focus on realigning the spine, typically by muscular relaxation or muscular or ligamentous stretching. However, such treatments, which include physical therapeutic, chiropractic, and bracing techniques, are inconsistently supported by current evidence. In this study, we assess the possible benefits of asymmetrical strengthening of truncal muscles on the convex side of the scoliotic curve through a single yoga pose, the side plank pose, in idi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 23 publications
1
34
1
2
Order By: Relevance
“…Yet, only a few studies have targeted patients with DLS. Daily side plank exercises on the side of curve convexity for 3-22 months were reported to reduce the curves significantly in 30% of the patients with ADIS and DLS [70]. The study, however, did not evaluate the impact of the exercises on pain and disabilities [70].…”
Section: Scoliosis-specific Exercisesmentioning
confidence: 94%
See 3 more Smart Citations
“…Yet, only a few studies have targeted patients with DLS. Daily side plank exercises on the side of curve convexity for 3-22 months were reported to reduce the curves significantly in 30% of the patients with ADIS and DLS [70]. The study, however, did not evaluate the impact of the exercises on pain and disabilities [70].…”
Section: Scoliosis-specific Exercisesmentioning
confidence: 94%
“…The poor outcomes of the above interventions are not unexpected, as the treatments were directed towards pain relief, but not the deformities and the global imbalance that are causing the symptoms [69]. Treatment approaches that target spinal deformities yielded better results in terms of reduction in pain and disability ratings in ADIS patients [70][71][72][73][74][75][76]. Yet, it has to be noted that many of the studies targeted younger cohorts who suffered from ADIS rather than DLS.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…A case report evaluating a twice-weekly, 12-week yoga intervention for an individual with SCI suggested that yoga may result in improvements in balance, strength, endurance, flexibility, posture, and functional outcomes 61. Yoga has also yielded benefits in individuals with scoliosis with respect to the degree of curvature of the spine, and there are now well-documented benefits for yoga reducing functional disability for chronic back pain 38,62. It has been suggested that Iyengar yoga (IY) be integrated into SCI rehabilitation therapies to increase physical functioning and to cultivate a positive mind–body experience 63.…”
Section: Introductionmentioning
confidence: 99%